Art, architecture and vanguard in the first peronism (2012)
This work addresses the links between the artists of theConcrete Avant-garde led by Tomás Maldonado and agroup of students of architecture of the Buenos AiresUniversity. From 1948 the group of artists and architectsconstituted a front for struggle for modern architectureand aesthetic and cultural renewal, and undertakes anumber of highly innovative and corrosive initiativeswhere merge art, architecture and design. In this context,are analyzed the fluctuating relations that the group engagedwith peronism, intending to complexify the mostwidespread historical vision on this period